Common Diseases in Bird; Letter to Editor - Ayesha Muazzam (Brilliance: Research of Artificial Intelligence, 2022)
I am writing this letter to you in order to bring light toward major diseases in poultry here in this letter I gave complete overview of major disease in poultry and also suggest about treatment There are some common diseases of Poultry some are viral, some are bacterial, some are fungal and some are parasitic